Meningkatkan Hasil Kemampuan Berhitung Pada Siswa Kelas III SDN 1 Tegalrejo Melalui Media Pohon Berhitung - Rizky, Aulia (Prosiding University Research Colloquium, 2021)
The purpose of this study was to improve the results of students' numeracy skills by usingthe media of counting trees. The research method used is Classroom Action Research(CAR) which consists of two cycles where each cycle has stages of planning, action,observation, and reflection. This research involved 5 students and was conducted at SDNegeri 1 Tegalrejo. Based on the test results, in the first cycle, there was the highest scoreof 90 and the lowest score of 70 with an average value of 77.5. While in the second cycle,the highest score was 100 and the lowest value was 90 and the average was 97.5. So it canbe concluded that the learning media tree counting can improve the results of numeracy.